Rasio Bekatul Padi dengan Pelarut pada Ekstraksi Minyak Bekatul Padi - Mas’ud, Fajriyati; Pabbenteng, Pabbenteng (Politeknik Negeri Ujung Pandang, 2016)
Rice bran oil is the oil extracted from rice bran. This is edible oil that is very good for health so that potential as a functional food, and can be develop the agroindustry. Solvent extraction process is done using n-heksane and ethanol. The purpose of this study was to determine the best ratio of rice bran with n-heksane and ethanol to obtain the highest percentage of the oil. The main ingredient of this study is rice bran, n-heksane and ethanol. The extraction process is done at a temperature of 55° C, 200 rpm for 5 hours. The results showed that the best ratio of bran and n-heksan to produce the ultimate percentage of oil is 1: 7 that is equal to 7,53%, as well as the best ratio of bran and ethanol to produce the ultimate percentage of oil is 1: 6 that is equal to 8,49%.